Resveratrol: A Potential Active Compound for Inflammatory Bowel Disease - Saraswati, Ni Wayan Citra Ayu; Nugraha, Gede Rama Hardy; Retnaningsih, Ekawaty; Afifah, Fiza; Firdaus, Silmi; Mutia, Baiq Marceliya Anjani; Mukhlishah, Neneng Rachmalia Izzatul (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Inflammatory Bowel Disease (IBD) is a chronic intestinal disorder consisting of Crohn’s Disease (CD) and Ulcerative Colitis (UC). The highest prevalence of IBD is found in Asia and the cases often occur in the 15-35 group of age. Conventional therapy options that are commonly used have some side effects that impact IBD patients. Therefore, it is necessary to look for new strategies in order to treat IBD regarding their effectiveness, affordability and achieving minimum side effects. Resveratrol, a natural non-flavonoid polyphenolic compound, is commonly found in grapes and various types of berries. It is known to potentially overcome inflammation in IBD through various mechanisms including acting as anti-inflammatory, antioxidant, immunomodulatory effects, and its ability to influence the gut microbiota. This study is aiming for explaining and reviewing further mainly on resveratrol’s extraction method and its mechanism of actions to improve IBD. The resources for this study are done by searching through PubMed, ProQuest, ScienceDirect, MDPI, and Google Scholar with keywords (Inflammatory Bowel Disease) AND (Resveratrol), ⁠(Incidence and Prevalence) of Inflammatory Bowel Disease across Asia, (Threat) AND (Therapy) AND (Inflammatory Bowel Disease), (Bioactive) AND (Therapy) AND (Inflammatory Bowel Disease), (Extraction) AND (Method) AND (Resveratrol), and (Pathophysiology) AND (Inflammatory Bowel Disease). Based on evidence found on resveratrol’s benefits, this compound is apparently promising to alternatively treat IBD, but still needs more research to support its effectiveness.